Identification of BR101549 as a lead candidate of non-TZD PPARγ agonist for the treatment of type 2 diabetes: Proof-of-concept evaluation and SAR. Issue 4 (15th February 2019) - Choung, Wonken; Jung, Hui Jin; Yang, Deokmo; Nam, Eun Hye; Choi, Hyukjoon; Lee, Bo Ram; Park, Min; Jang, Su Min; Lim, Jae Soo; Kim, Woo Sik; Kim, Kyung-Hee; Chin, Jungwook; et al.
Graphical abstract: Abstract: The new class of PPARgamma non-TZD agonist originally derived from the backbone of anti-hypertensive Fimasartan, BR101549, was identified as a potential lead for anti-diabetic drug development. The X-ray crystallography of BR101549 with PPARgamma ligand binding domain (LBD) revealed unique binding characteristics versus traditional TZD full agonists. The lead candidate, BR101549, has been found activating PPARgamma to the level of Pioglitazone in vitro and indeed has demonstrated its effects on blood glucose control in mouse proof-of-concept evaluation. The attempts to improve its metabolic stability profile through follow-up SAR including deuterium incorporation have been also described.